Pengathe Effect Of Human Resources Competence On Civil Servant Performance Mediated By Motivation At The Diskoperindag Of Bungo District - Misra Yeni; Erick Muhammad Henriza; Ida Zuliyana; Amran Amran (PT. Anagata Sembagi Education, 2025)
The purpose of this study is to analyze the influence of Human Resources (HR) Competence on Civil Servant (PNS) Performance mediated by Motivation at the Department of Cooperatives, SMEs, Industry and Trade of Bungo Regency. The research method used in this study is Descriptive Quantitative with a population and sample of 34 respondents (saturated sampling). Research data analysis was carried out using Partial Least Square (PLS) 4.0. The results of the study indicate that directly (direct effect) HR Competence has a significant effect on Performance HR Competence has a significant effect on Motivation Then Motivation has no significant effect on Performance While indirectly (Indirect Effect) obtained Motivation cannot mediate the influence of HR Competence on Civil Servant Performance at the Department of Cooperatives, SMEs, Industry and Trade of Bungo Regency.